The Curse of Tobacco - Pathak, Vishal; R. Singh, (Ms); Pathak, Prabhat (Asian Journal of Chemistry, 2010)
Tobacco smoking is a social evil since it is the main cause of pulmonary diseases and also affects the economy of the society. The present report deals with the hazards of tobacco and suggestions have also been made to remove this evil. It is obvious from this study that most of the burden of disease in the coming years will fall on current smokers which signifies the importance of programmes dealt here to support its cessation.